Low-cost step aerobics system with virtual aerobics trainer - Rosa, Alejandro; Barbancho-Pérez, Isabel; Tardón-García, Lorenzo José; Barbancho-Pérez, Ana María (My University, 2014)
In this paper a low-cost step-aerobics instructor simulation system is presented. The proposed system analyses a given song to iden- tify its rhythmic pattern. Subsequently, this rhythmic pattern is used in order to issue a set of steps-aerobics commands to the user, thus simu- lating a training session. The system uses a Wii Balance Board to track exercises performed by users and runs on an Android smartphone. A set of tests were conducted to assess user experience and opinion on the system developed.
Keywords: Interacción hombre-ordenador; Videojuegos; Human-computer interaction; Music information retrieval; Signal processing